Analyzing Audit Quality Indicators in Audit Companies in Indonesia - Pina, Pina; tian, Chris; Silvana, Versia (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2023)
Because of the high level of confidence established by audit reports and the services given by auditors, public accounting firms, particularly those with extremely large scales, must pay greater attention to the quality of the audit to be performed. The purpose of this study is to talk about audit quality using audit reports from PT Atic Anabatic Technologies Tbk and PT Arna Arwana Citra Mulia Tbk. The services of KAP partners Purwantono, Sungkoro, and Surja, who hail from the BIG 4, Ernst Young Public Accounting Firm, were used to perform qualitative research based on the findings of each organization about the timing of the audit (EY). Each auditor, however, prepares audit reports at various times. According to what was previously said, Susanti had a 147-day audit delay, whereas Benyanto Suherman experienced a 33-day audit delay. Because the quality of an audit provided by an auditor is not only measured by the time in which the audit report is carried out; it is also measured by several components of audit quality indicators, such as journalists, auditors, ethics, auditor independence, policies, service imbalances, and so on, it cannot be directly concluded based on the conditions that occur.